Histopathological analysis of tumours and tumour-like lesions of colon and rectum - Pramila Vaidhya (Journal of Pathology of Nepal, 2020)
Background: Tumours and tumour like lesions of the colon and rectum have overlapping clinical presentation and may be difficult to diagnose on clinical grounds alone. Histopathological examination although helpful to arrive at correct diagnosis, at times may be difficult and may require ancillary tests such as immunohistochemistry.